1973
DOI: 10.1083/jcb.59.3.633
|View full text |Cite
|
Sign up to set email alerts
|

A Scanning Electron Microscope Study of Surface Features of Viral and Spontaneous Transformants of Mouse Balb/3t3 Cells

Abstract: Cells of the mouse line Balb/3T3 as well as three virus-induced transformants and two spontaneous transformants grown in vitro have been studied for their topography by scanning electron microscopy . The parent cell in confluent culture closely resembles an endothelial cell in its form and in the structure of its association with adjacent cells . The tumorigenic transformants produced by SV40, murine sarcoma virus, or polyoma viruses are fusiform to pleomorphic and distinctly different from the cell of origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(48 citation statements)
references
References 25 publications
6
42
0
Order By: Relevance
“…5). Because vascular endothelial cells are bathed in undiluted (100%) plasma in vivo, our evidence that BALB/ c 3T3 cells starve in medium containing an interstitial concentration (10%) of plasma-derived human serum is consistent with the published evidence suggesting that BALB/c 3T3 cells are endothelial in nature (15,16 (17) have demonstrated that, unlike aneuploid, highly cultureselected 3T3 cells, diploid-human fibroblasts proliferate actively in plasma-containing media.…”
Section: Resultssupporting
confidence: 79%
“…5). Because vascular endothelial cells are bathed in undiluted (100%) plasma in vivo, our evidence that BALB/ c 3T3 cells starve in medium containing an interstitial concentration (10%) of plasma-derived human serum is consistent with the published evidence suggesting that BALB/c 3T3 cells are endothelial in nature (15,16 (17) have demonstrated that, unlike aneuploid, highly cultureselected 3T3 cells, diploid-human fibroblasts proliferate actively in plasma-containing media.…”
Section: Resultssupporting
confidence: 79%
“…The fibrinolytic activity exhibited by the established endothelial cell line seems to reflect a physiological characteristic of the intimal layer from which it is derived rather than a property acquired during the culture period as a result of spontaneous transformation because: (i) the growth pattern and the morphology of the established endothelial cell line are the same as those of the primary culture from which it is derived; in contrast, spontaneous transformants of Balb/3T3 cell line [an embryonic mouse cell line of endothelial derivation (21)] are distinctly different from the nontransformed parental line with respect to cell surface and growth pattern (21); and (ii) the endothelial cell line from rabbit aorta is not tumorigenic when tested in the immunologically incompetent (athymic) mouse. The fibroblast line (a normal, nontransformed cell line as demonstrated by its inability to form tumor in the nude mouse) has no significant fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 4 is actually a picture of a cell incubated with 5 ,gg/ml of cycloheximide from the time of the shift from 410 to 36' until fixation 2 hr later. In a control experiment we have shown that under these conditions the level of incorporation of radioactive leucine into protein in the presence of cycloheximide is only 1% of that occurring in its absence.…”
Section: Resultsmentioning
confidence: 99%